1987
DOI: 10.3109/10715768709088086
|View full text |Cite
|
Sign up to set email alerts
|

Damage of Erythrocytes by Activated Oxygen Generated in Hypoxic Rat Liver

Abstract: The implication of activated oxygen in the interaction between hypoxic rat liver and circulating erythrocytes was investigated. Reduced species of oxygen generated in hypoxic liver owing to accelerated purine nucleotide degradation via xanthine oxidase initiate alterations of plasma membrane and glutathione system of erythrocytes. Osmotic fragility, hemolysis rate and erythrocytic GSSG:GSH ratio may be considered as appropriate indicators of oxidative load in liver and other tissues. Addition of erythrocytes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…40 A study in rats showed that an increase in ROS in liver initiated changes in the erythrocytic GSH/GSSG ratio; the authors concluded that the erythrocytic GSH/GSSG ratio reflects oxidative stress in liver and other tissues. 41 Additionally, an intact transsulfuration pathway has been identified in blood cells, including macrophages 42 and T cells, 43 and transsulfuration pathway flux is upregulated in naïve and activated T cells after exposure to peroxide. 43 Even concentrations, folic acid as pteroylglutamic acid was used for calibration, and its 125 I-labeled analog was used as the tracer; for vitamin B 12 , cyanocobalamin was used for calibration, and its 57 Co-labeled analog was used as the tracer.…”
Section: Discussionmentioning
confidence: 99%
“…40 A study in rats showed that an increase in ROS in liver initiated changes in the erythrocytic GSH/GSSG ratio; the authors concluded that the erythrocytic GSH/GSSG ratio reflects oxidative stress in liver and other tissues. 41 Additionally, an intact transsulfuration pathway has been identified in blood cells, including macrophages 42 and T cells, 43 and transsulfuration pathway flux is upregulated in naïve and activated T cells after exposure to peroxide. 43 Even concentrations, folic acid as pteroylglutamic acid was used for calibration, and its 125 I-labeled analog was used as the tracer; for vitamin B 12 , cyanocobalamin was used for calibration, and its 57 Co-labeled analog was used as the tracer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to protecting the host cell, erythrocyte glutathione (GSH) can also efficiently defend other tissues (e.g., lung, liver) [41,47]. The protective mechanism by GSH results in an increased formation and subsequent translocation into plasma of oxidized glutathione (GSSG).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to protecting themselves, eythrocytes can efficiently defend lung, liver and the immature tissues of premature infants from oxidant attack [10][11][12]. Tracheal insufflation of a small number of intact erythrocytes prevents oxidative lung injury, glutathione having been the beneficial erythrocyte constituent [10].…”
Section: Introductionmentioning
confidence: 99%